STRATEGI INTERNATIONAL LABOUR ORGANIZATION (ILO) DALAM MENANGANI MASALAH PEKERJA ANAK DI INDONESIA TAHUN 2017 – 2020 - Dinda Elmas; Ahmad Fuadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study aims to analyze the strategy of the International Labour Organization (ILO) through its role as an international organization in addressing the problem of child labor in Indonesia via the implementation of child labor elimination programs throughout 2017 to 2020. The ILO defines child labor as a social problem which can interfere with a child's mental and physical development. Based on data from the Central Statistics Agency (BPS) in 2017, the number of child workers in Indonesia reached over 1.2 million children. Poverty is the main driving factor for child labor in Indonesia. This study utilized a qualitative methodology with data collection techniques by library studies that have sourced from books, journals, reports, articles and websites. This study similarly used the perspective of Pluralism and the theory of International Organizations Role. The results of this study indicated that the International Labour Organization (ILO) has an important role in executing its strategy in dealing with child labor issue in Indonesia which accordingly is demonstrated from the implementation of programs for the elimination of child labor. These exclusive programs in the framework of the ILO-IPEC (International Programme on the Elimination of Child Labor) which succeeded in reducing the number of child labor by 21.14% in 2018, ILO-PROMOTE (Countering Child Labor in the Domestic Sector in Indonesia) was an achievement in reaching many partners to dissolve domestic workers and child domestic workers in Indonesia through community socialization aside from media publications and The collaborative ILO-IPEC's support program for Indonesia's CCT (Conditional Cash Transfer) program, namely PKH (Family Hope Program), resulted in an increase in school enrollment and participation of children from poor families during 2019 to 2020. Keywords: Child Labor, ILO-IPEC, ILO-PROMOTE, PKH.